Temporal Disruptions And Oneiric States: An Epistemological Inquiry Into Lucid Dreaming In Pendulum - Dr. Saran S.; Dr. BasilThomas; Dr. GemCherian (Educational Administration: Theory and Practice, 2024)
Dream enthusiasts and researchers are drawn to lucid dreaming, a unique state of awareness in which the dreamer is aware that he is dreaming and has influence over the dream world. A thorough examination of the state of dream research today is given in this review article, which covers a wide range of topics including the neurological underpinnings of the phenomena, induction techniques, clinical applications, and advantages and disadvantages related to it. Pendulum (2023), as the title suggests, deliberately employs a clear allusion to the idea of “time,” establishing it as the main character in the story. The word “pendulum,” which means “measured movements of a pendulum”, acts as a metaphorical anchor, signifying the rhythmic oscillation and sway of time. This article attempts to better understand lucid dreaming and its effects on psychology, neuroscience, and health by summarising important research and conclusions.